Analysis of factors influencing the clinical outcome after surgery and 131I therapy in patients with moderate-risk thyroid papillary carcinoma - Li, Yixuan; Rao, Maohua; Zheng, Chenxi; Huang, Jiahui; Fang, Danzhou; Xiong, Yalan; Yuan, Gengbiao (Frontiers in Endocrinology, 2022)
Purpose：Papillary thyroid cancer (PTC) usually has a favorable prognosis.However, moderate risk requires further evaluation. Therefore, this study investigated the clinical outcomes in patients with moderate-risk PTC following surgery and the first 131I therapy, as well as the relevant factors that influence the therapeutic effect. Methods：Retrospective analysis of 135 patients with medium-risk PTC who visited the Second Affiliated Hospital of Chongqing Medical University from January 2018 to April 2019.According to the 2015 American Thyroid Association (ATA) guideline treatment response evaluation system,patients were divided into excellent response (ER) group, indeteriminate response (IDR) group, biochemical incomplete response (BIR) group,and structurally incomplete response (SIR) group , of which IDR, BIR, and SIR are collectively referred to as the NER group. To compare the general clinical features of the two groups of patients, two independent samples t test, χ2 test, and Mann-Whitney U test were utilized, followed by multivariate logistic regression analysis. Using the receiver operating characteristic (ROC) curve, the predicted value of ps-Tg to ER was evaluated, and the best cut-off value was determined. Results：The treatment responses of 94 patients were ER, and those of 41 were NER.the differences in tumor size（U＝1491.50）,the number of metastatic lymph nodes（U＝1422.00）,metastatic lymph node size（U ＝1396.50）,metastatic lymph node ratio（U=1441.50）、metastatic lymph node location（χ2=7.40）,ps-Tg level（U＝680.00）were statistically significant.Multivariate regression analysis showed that ps-Tg (OR=1.200，95% CI：1.107 1.302）was an independent factor affecting ER.The cut-off value of ps-Tg for predicting ER was 7.38ug/L, and its sensitivity and specificity were 68.3% and 87.2% respectively. Conlusions：Patients with smaller tumor size, fewer lymph nodes, lower metastatic lymph node ratio, metastatic lymph nodes in the central region,smaller lymph node size, and ps-Tg <7.38 ug/L have better therapeutic effect after initial treatment.